2021
DOI: 10.3390/atmos12091086
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fossil Fuel Combustion Metals in PM2.5 Air Pollution Health Associations

Abstract: In this review, we elucidate the central role played by fossil fuel combustion in the health-related effects that have been associated with inhalation of ambient fine particulate matter (PM2.5). We especially focus on individual properties and concentrations of metals commonly found in PM air pollution, as well as their sources and their adverse health effects, based on both epidemiologic and toxicological evidence. It is known that transition metals, such as Ni, V, Fe, and Cu, are highly capable of participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 168 publications
0
36
0
Order By: Relevance
“…This allows metals to participate in redox reactions that contribute to oxidative stress and adverse health effects . A recent review by Maciejczyk, Chen, and Thurston further discusses this relationship and concludes that fossil fuel combustion emissions are among the greatest contributors to adverse health effects …”
Section: Evidence For the Differential Toxicity Of Ambient Pm25 By So...mentioning
confidence: 99%
See 1 more Smart Citation
“…This allows metals to participate in redox reactions that contribute to oxidative stress and adverse health effects . A recent review by Maciejczyk, Chen, and Thurston further discusses this relationship and concludes that fossil fuel combustion emissions are among the greatest contributors to adverse health effects …”
Section: Evidence For the Differential Toxicity Of Ambient Pm25 By So...mentioning
confidence: 99%
“…61 A recent review by Maciejczyk, Chen, and Thurston further discusses this relationship and concludes that fossil fuel combustion emissions are among the greatest contributors to adverse health effects. 62 Studies of indoor/household PM 2.5 could provide some additional insights. A large cohort study in rural China by Yu et al, for example, found that household cooking and heating with wood (including charcoal) was more toxic than coal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…53 SRM-1648a has been widely used because of its certied composition and the connection it enables across various studies that are not possible with variable PM composition. [54][55][56][57][58][59][60][61][62] SRM-1648a contains dozens of metals whose concentrations are given in Table S1. † An aqueous stock solution of the urban PM extract was prepared by adding 200 mg of SRM-1648a to 200 mL of 0.1 N HNO 3 , stirred at 200 rpm for 24 hours, and vacuum ltered (Tissue Quartz 2500 qat-up lter).…”
Section: Nist Urban Pm-srm-1648a Extractmentioning
confidence: 99%
“…According to the Paris agreement and also a report released by Intergovernmental Panel on Climate Change (IPCC) [3], a large portion of carbon dioxide is sourced from the industrial sector and transportation showing that the current pathway of combustion of fossil fuels will not be sustainable [4]. Combustion of fossil fuels releases air pollutants such as NOx, CO2 [5], and particulate matter (PM2.5) [6], which results in air pollution, environmental damage and intensification of global warming. Therefore, there is a need to further develop energy production systems together with seeking alternative energy resources such as renewable energy to replace fossil fuels and avoid pollutions associated with their combustion.…”
Section: Introductionmentioning
confidence: 99%